(untitled) (Actualizaciones en Sida e Infectología, 2024)
Western equine encephalitis (WEE) is a re-emerging dis-ease in Argentina starting in 2023. Since the initial notifi- cation in 1933, the last epizootics occurred in 1983, and the last human case was recorded in 1996.The characteristics of the causative agent, the ecology with special reference to vectors identified in the country, their competence in transmission, and the cycle as well as the risks factors for acquiring the disease, are reviewed. The epidemiological situation in horses and humans from November 2023 to March 2024 is analyzed. The clinical presentation of the human disease, its evolutionary potential, available data in confirmed cases, and the treatment are described.The methodology and algorithm used for the etiological diagnosis at the National Reference Center are detailed. Strategies for prevention and control are based on vaccination of horses, environmental sani- tation and outbreak control in the presence of the animal disease (active epidemiological surveillance).